Children's economic development: an empirical survey of children from a Slovak town - Rinkovská Jana (My University, 2008)
The main idea of this study was to test the theories and ideas developed by Webley et al.(2001), The Economic Psychology of Everyday Life, and to compare research from Slovakia with the study from a Polish town. Four different questionnaires, which were created by Jakub Dziekonski at WSB-NLU and then slightly modified to fit the Slovak conditions, were surveyed among four different age-groups of children. 120 questionnaires were equally distributed among the four groups: the pre-school period, the school entry period, the school period: (9- 10 years old), and the school period: (10-14 years old). Apart from the fact that each nation has its own cultural and economical differences, all four groups, which were surveyed in Slovakia, follow the same developmental and economic patterns as the equivalent British example described by Webley et. al (2001) and Jakub Dziekonski’s study carried out in a small Polish town.
Rozwój świadomości ekonomicznej dzieci: badania ankietowe w małym polskim miescie
Keywords: economic development; children; survey